DOP80 Oral curcumin is not more effective than placebo to prevent endoscopic postoperative recurrence in patients with Crohn's disease treated with concomitant thiopurines: the POPCUR trial. (25th January 2019) - Buisson, A; Laharie, D; Nancey, S; Hébuterne, X; Roblin, X; Nachury, M; Peyrin-Biroulet, L; Fumery, M; Goutorbe, F; Coban, D; Allimant, C; Reymond, M; et al.
Abstract: Background: Postoperative recurrence is a major concern in patients with Crohn's disease (CD). Curcumin exhibited anti-inflammatory and anti-oxidative properties in cellular and rodent models. Recently, a randomised controlled trial demonstrated that oral curcumin was more effective than placebo to induce clinical and endoscopic remission in patients with ulcerative colitis failing to mesalamine. 1 We aimed to assess the efficacy of oral curcumin compared with placebo to prevent endoscopic POR in patients with CD receiving concomitant thiopurines therapy. Methods: We conducted a double-blind, randomised, placebo-controlled trial in eight IBD centres. All patients with CD (> 18 years old) undergoing bowel resection were consecutively enrolled within 15 days after the surgery or the closure of diverting stoma. All macroscopic lesions had to be removed and the anastomosis had to be reached by colonoscopy. The patients were randomised to be treated with azathioprine 2–2.5 mg/kg, and either placebo (placebo group) or oral curcumin (3 g/day) (curcumin group). The primary endpoint was endoscopic POR at 6 months (M6), defined as Rutgeerts' index ≥ i2a. Secondary endpoints were severe endoscopic POR (≥ i3), clinical POR (CDAI > 150), quality of life (IBDQ) and safety. An intermediary analysis was planned after the enrolment of 50% of the patients ( n = 62 patients). Results: Overall, 62 patients were enrolled (mean age 36.3 ± 12.0 years, mean CD duration 8.1 ans ± 8.0 years, 67.2% female genders, 37.8% smokers, 8.2% with perianal lesions, 45.9% with structuring CD, 36.1% with fistulizing CD, 45.9% with prior bowel resection, 18.0% of anti-TNF naïve patients). In intermediary analysis (intent-to-treat), curcumin was not more effective than placebo to prevent endoscopic POR at M6: 67.7% (21/31) vs. 58.1% (18/31) ( p = 0.60), in curcumin and placebo groups, respectively. The rate of severe endoscopic POR was significantly higher in patients treated with curcumin (17/31, 54.8%) compared with placebo (8/31, 25.8%) ( p = 0.02). The rate of clinical POR was not different between the two groups: 38.7% (12/31) in curcumin group vs. 45.2% (14/31) in placebo group ( p = 0.80). IBDQ was similar between the two groups (178.5 in the curcumin group vs. 181.5 in the placebo group; p = 0.63). The rate of adverse events was not different between the two groups. Conclusions: Oral curcumin was not more effective than placebo to prevent endoscopic postoperative recurrence (POR) in patients with CD receiving concomitant thiopurines therapy. Reference 1. Lang A et al. 2015. Clin Gastroenterol Hepatol